Exosomes Mediate the Production of Oxaliplatin Resistance and Affect Biological Behaviors of Colon Cancer Cell Lines - Ye, Yanwei; Li, Yingze; Wu, Chu; Shan, Yiming; Li, Jie; Jiang, Dongbao; Li, Jingjing; Han, Chao; Liu, Dongdong; Zhao, Chunlin (Current Cancer Drug Targets, 2025)
BackgroundColon cancer has high mortality rate which making it one of the leading causes of cancer deaths. Oxaliplatin is a common chemotherapeutic drug, but it has disadvantages such as drug resistance.ObjectiveThe purpose of this study is to explore the mechanism of exosomes in the resistance of oxaliplatin and verify whether elemene and STAT3 inhibitors reverse the resistance to oxaliplatin.MethodsRelated cell line models were constructed and the proliferation, migration, invasion, apoptosis and resistance to oxaliplatin were evaluated for all three cells of HCT116/L, sensitive cell HCT116 and HCT116+HCT116/L-exosomes (HCT116-exo). It was to explore probable signaling pathways and mechanisms by Western blotting.ResultsHCT116-exo drug-resistant chimeric cells showed greater capacity for proliferation, migration and invasion than HCT116 sensitive cells. After the above cells were treated with oxaliplatin, the apoptosis rate of chimeric drug-resistant cells HCT116-exo and its IC50 increased compared with the sensitive cells HCT116. The proliferation, invasion and migration of cells treated with STAT3 inhibitor or β-elemene combined with oxaliplatin reduced compared with those treated with oxaliplatin or β-elemene alone. The STAT3 inhibitor or β-elemene in combination with oxaliplatin increased the rate of apoptosis relative to oxaliplatin or β-elemene alone. Drug-resistant cell exosomes could promote the EMT process, related to the participation of FGFR4, SHMT2 and STAT3 inhibitors.ConclusionDrug-resistant cell exosomes could induce resistance, and improve the capacity of colon cancer towards proliferate, invade, migrate and promote the EMT process. The β-elemene combined with oxaliplatin could reverse the above results which might be related to the STAT3 pathway and EMT pathway in colon cancer.
Keywords: oxaliplatin